Le contrat sexuel - Pateman, Carole (La Découverte Poche, 2022)
« Par quel étrange paradoxe le contrat social, censé instituer la liberté et l'égalité civiles, a-t-il maintenu les femmes dans un état de subordination ? Pourquoi, dans le nouvel ordre social, celles-ci n'ont-elles pas accédé, en même temps que les hommes, à la condition d'« individus » émancipés ? Les théories du contrat social, héritées de Locke et de Rousseau, et renouvelées depuis Rawls, ne peuvent ignorer les enjeux de justice que soulève le genre. Carole Pateman montre, dans cet ouvrage désormais classique, que le passage de l'ordre ancien du statut à une société moderne du contrat ne marque en rien la ﬁn du patriarcat. La philosophe met ainsi au jour l'envers refoulé du contrat social : le « contrat sexuel », qui, via le partage entre sphère privée et sphère publique, fonde la liberté des hommes sur la domination des femmes. Il s'agit là moins d'exploitation que de subordination, comme le démontre l'autrice en analysant le contrat de mariage, mais aussi l'ensemble des contrats touchant à la propriété de la personne, de la prostitution à la maternité de substitution, jusqu'à l'esclavage et au salariat. Ainsi s'engage, à partir du féminisme, une critique de la philosophie politique libérale dans son principe même : pour Carole Pateman, un ordre social libre ne peut en aucun cas être de type contractuel. »-- Quatrième de couverture.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; citoyenneté; contrat social; cours; discipline; droits des femmes*; fem1000; histoire et politique; incontournable; justice sociale; outils; ouvrages de références; patriarcat; phi4336; philosophie; philosophie politique; pol4212; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; théories féministes; violences; états-unis

The feminist case against pornography: a review and re-evaluation - Cawston A. (Inquiry (United Kingdom), 2019)
Despite sustained feminist criticism, the production and consumption of pornography does not show signs of waning. Here, I offer a critical review of the existing feminist anti-pornography debate, arguing that it has largely failed to provide suitable grounds for a stable and comprehensive critique, instead often indirectly providing theoretical resources for pornography to reinvent itself. This is a product, in my view, of a misguided focus on the pornographic object. Feminist critics are better served, I argue, by redirecting their critical gaze towards the consumers of pornography, and, in particular, to the attitudes such consumption reflects. To that end, I introduce an alternative, attitudinal approach that enables criticism of pornography as a reflection of sexist attitudes, as well as for its role in concealing these attitudes.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; philosophie; philosophie politique; pornographie; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; éthique

The SAGE handbook of feminist theory - Evans, Mary (SAGE reference, 2014)
At no point in recorded history has there been an absence of intense, and heated, discussion about the subject of how to conduct relations between women and men. This Handbook provides a comprehensive guide to these omnipresent issues and debates, mapping the present and future of thinking about feminist theory. The chapters gathered here present the state of the art in scholarship in the field, covering: Epistemology and marginality; Literary, visual and cultural representations; Sexuality; Macro and microeconomics of gender; Conflict and peace. The most important consensus in this volume is that a central organizing tenet of feminism is its willingness to examine the ways in which gender and relations between women and men have been (and are) organized. The authors bring a shared commitment to the critical appraisal of gender relations, as well as a recognition that to think ‘theoretically’ is not to detach concerns from lived experience but to extend the possibilities of understanding. With this focus on theory and theorizing about the world in which we live, this Handbook asks us, across all disciplines and situations, to abandon our taken-for-granted assumptions about the world and interrogate both the origin and the implications of our ideas about gender relations and feminism. It is an essential reference work for advanced students and academics not only of feminist theory, but of gender and sexuality across the humanities and social sciences.
Keywords: approches et analyses; corps; cours; discipline; har4600; histoire et politique; intersectionnalité; outils; ouvrages de références; philosophie; phénoménologie; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences de la gestion; sciences humaines; sciences sociales; sex1911; thématiques; violences; économie; épistémologie; études féministes

Traite, prostitution, inégalité - MacKinnon, Catharine A. (Collection Mobilisations, 2014)
De nos jours, il n'y a pas plus de prise de position favorable à la traite des êtres humains à des fins d'exploitation sexuelle qu'il y a de prise de position publique pour l'esclavage. Il est également très difficile de trouver des partisanes déclarées de l'inégalité… Ce n'est pourtant pas le cas de la prostitution. Certaines personnes sont pour la prostitution. Plus nombreuses sont celles qui considèrent politiquement correct de la tolérer. La plupart présument que, même si elle n'est pas réellement souhaitable, la prostitution est nécessaire, inévitable et sans dommage. Est-ce que la décriminalisation du proxénétisme et la légalisation des maisons closes assureront une plus grande sécurité physique aux personnes prostituées ? Contrairement à la Cour suprême du Canada, la juriste de réputation mondiale, Catharine A. Mac- Kinnon, répond négativement à cette question. Elle soutient que « loin de rendre la vie des prostituées plus sûre, la décriminalisation totale de la prostitution peut même la rendre encore plus dangereuse ». Pour cela, elle s'appuie sur les expériences des pays qui ont légalisé la prostitution et le proxénétisme et sur celles des pays, de plus en plus nombreux, qui décriminalisent les personnes prostituées et pénalisent les clients-prostitueurs ; la stigmatisation liée à l'activité Prostitutionnelle se retourne désormais contre ceux qui en profitent : les prostitueurs et les proxénètes.
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; droits des femmes*; inégalités; justice sociale; patriarcat; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; travail du sexe-prostitution; violences

Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." -- Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles